Opportunities of the Intervention of the Central (Regional) Government in the Decisions and Operations of the Local Governments in Hungary - Istva´n Hoffman (Теоретическая и прикладная юриспруденция)
The regulation on the relationship of the central and local governments in Hungary has transformed significantly in the last decade. However, the government have strong tools for the control of the local activities, these tools are just rarely applied by the supervising authorities. The main transformation of that relationship could be observed in the field of the public service provisions. The former municipally based public service system was transformed into a centrally organised and provided model, thus the role of the local governments in Hungary has decreased. The centralisation process have been strengthened by the reforms during the COVID-19 pandemic.